Associations between eating speed and food temperature and type 2 diabetes mellitus: a cross-sectional study - Lu, Yan; Liu, Jia; Boey, Johnson; Hao, Ruiying; Cheng, Guopeng; Hou, Wentan; Wu, Xinhui; Liu, Xuan; Han, Junming; Yuan, Yuan; Feng, Li; Li, Qiu (Frontiers in Nutrition, 2023)
Objective: This study aimed to evaluate the relationship between eating speed and food temperature and type 2 diabetes mellitus (T2DM) in the Chinese population. Methods: A cross-sectional survey was conducted between December 2020 to March 2022 from the department of Endocrinology at the Shandong Provincial Hospital. All recruited participants were asked to complete structured questionnaires on their eating behaviors at the time of recruitment. Clinical demographic data such as gender, age, height, weight, familial history of T2DM, prevalence of T2DM and various eating behaviors were collected. Univariate and multivariate logistic regression analyses were used to analyze the associations between eating behaviors and T2DM. Results: A total of 1040 Chinese adults were included in the study, including 344 people with T2DM and 696 people without T2DM. Multivariate logistic regression analysis of the general population showed that gender (OR=2.255, 95% CI: 1.559-3.260, P<0.001), age (OR=1.091, 95% CI: 1.075-1.107, P<0.001), BMI (OR=1.238, 95% CI: 1.034-1.483, P=0.020), familial history of T2DM (OR=5.709, 95% CI: 3.963-8.224, P<0.001), consumption of hot food (OR=4.132, 95% CI: 2.899-5.888, P<0.001)，consumption of snacks (OR=1.745, 95% CI: 1.222-2.492, P=0.002), and eating speed (OR=1.292, 95% CI:1.048-1.591, P=0.016) were risk factors for T2DM. Conclusion: In addition to traditional risk factors such as gender, age, BMI, familial history of T2DM, eating behaviors associated with Chinese culture, including consumption of hot food, consumption of snacks, and fast eating have shown to be probable risk factors for T2DM.